Health Matters - Coasters Association (2007)
Number of pages: 20

Kids Summer Camp - Newcombe, Vanessa (Coasters Association, 2007)
In the summer of 2006, we embarked on a six (6) week summer camp pilot project in the Municipalities of Bonne Esperance and St. Augustine to provide a Youth Summer Camp for children between the ages of six to twelve. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS” has proven to be a great success. This year the goal was to expand our efforts to include the communities of Chevery, La Tabatiere, and Blanc Sablon, as well as to continuing the camps already established (St. Augustine, St. Paul’s River).

Seniors are an Asset for Quebec - Lincoln, Clifford (2007)

Consultation publique sur les conditions de vie des aînes : Un enjeu de société, une responsabilité qui nous interpelle tous - Conseil catholique d'expression anglaise (2007)
Le Conseil catholique d’expression anglaise aimerait féliciter le gouvernement du Québec pour avoir reconnu l’importance des problèmes affectant les aînés et notre population vieillissante et pour avoir créé le poste de ministre responsable des Aînés. Nous accueillons avec plaisir l’initiative de Mme Marguerite Blais, ministre responsable des Aînés, de tenir des audiences publiques sur les conditions de vie des aînés au Québec. Cet enjeu constitue une grande source de préoccupations pour notre communauté et pour ses institutions au service des personnes âgées, dont l’expérience dans ce domaine est considérable.

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

Primary Health Care: Survival Pack - Buckle, Heidi (2007)

Services to the Intellectually and Physically Challenged on the Lower North Shore - Buckle, Heidi (Coasters Association, 2007)

Mémoire présenté par le Conseil catholique d’expression anglaise sur les conditions de vie des aînés - The English Speaking Catholic Council (ESCC) (2007)